(untitled) (Faridpur Medical College Journal, 2011)
Ventricular tachycardia (VT) & ventricular fibrillation (VF) are the most common immediate life threatening complications after acute myocardial infarction. These complications occur in about 5-10% of patients who admitted in hospital and are thought to the major causes of death who die before reaching hospital and to take medical attention. Immediate defibrillation will usually restore sinus rhythm. Prompt pre-hospital resuscitation and defibrillation can save many more lives. Our patient, Mr. Abdul Malek, aged about 55years, hailing from west Naodoba, Jajira, Sariotpur, non-hypertensive, non-diabetic, smoker was admitted in MMW, FMCH on 23/03/10 with the complaints of chest discomfort, shortness of breath, sweating and vomiting. During admission his pulse and BP was non-recordable, ECG shows VT. Immediately the patient was transferred to CCU from MMW. Patient was kept in cardiac monitor and arranged for DC shock. After giving 200 joules DC shock patient reverted to sinus rhythm .His pulse was recordable and reasonable blood-pressure was regained. Then the patient was treated with antiplatelets, anti-coagulant, nitrates and prophylactic iv Lignocaine. Subsequently oral anti-arrhythmic drug Amiodarone was started. The recovery of the patient was un-eventful and was discharged after 10 days without any further complication. DOI: 10.3329/fmcj.v5i2.6828 Faridpur Med. Coll. J. 2010;5(2):72-73